Predicting worse survival for newly diagnosed T cell lymphoma based on the decreased baseline CD16−/CD16 + monocyte ratio - Wei Zhang (Nature Portfolio, 2020)
Abstract T cell non-Hodgkin lymphoma (T-NHL) is highly invasive and heterogeneous without accurate prognosis prediction. We proposed peripheral CD16−/CD16 + monocytes the additional indicators for T-NHL prognosis. We prospectively recruited 31 T-NHL patients without previous treatment. The CD16−/CD16 + monocyte ratio before chemotherapy was calculated and regular follow up was performed to calculate prognostic prediction value. Tumor associated macrophages (TAM) in tumor tissue were counted and transcriptome sequencing of CD16− and CD16 + monocytes was applied to explore potential mechanisms. We found that T-NHL patients had higher ratio of total monocytes especially the CD16 + monocytes along with a decreased ratio of CD16−/CD16 + monocytes, compared to the health control. The 1-year overall survival rate was 0.492 and 0.755 for CD16− monocyte/CD16 + monocyte ratio of <11 and ≥11(p < 0.05), respectively. The peripheral CD16−/CD16 + monocyte ratio was significantly relevant with the pathological CD68/CD206 macrophage ratio. The differently expressed genes in CD16− and CD16 + monocytes from T-NHL patients were mainly involved in signaling molecules related to tumor microenvironment. Pro-tumor genes were identified in monocyte subsets especially in CD16 + monocytes. In conclusion, the ratio of peripheral CD16−/CD16 + monocyte helps to stratify the prognosis of T-NHL. The relatively increased CD16 + monocytes may contribute to the pro-tumor microenvironment of T-NHL.